2018
DOI: 10.4236/ijoc.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approach for Novel Fluorine Substituted <i>α</i>-Aminophosphonic Acids Containing 1,2,4-Triazin-5-One Moiety as Antioxidant Agents

Abstract: Novel fluorine substituted α-amino phosphonic acids containing 1,2,4-triazin-5-one (6a-f) have been obtained from fluoroacylation of 6-(2ʹ-amino-5ʹ-nitrophenyl)-3-thioxo-1,2,4-triazin-5(4H)-one (1) followed by ammonilysis to give the corresponding 3-amino-derivative 3. Condensation of compound 3 with nitro/halogenated aromatic aldehydes yielded the Schiff bases 4. The simple addition of diethyl phosphonate to compound 4 produced the α-amino phosphonates 5. Acidic hydrolysis of compound 5 produced the fluorine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…TLC analyses were performed on Merck silica gel 60 F254 aluminum plates with hexane/ethyl acetate mixtures. Compounds 1 and 2 were obtained according to the reported method 9 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TLC analyses were performed on Merck silica gel 60 F254 aluminum plates with hexane/ethyl acetate mixtures. Compounds 1 and 2 were obtained according to the reported method 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the newly synthesized lamotrigine analogs (7)(8)(9)(10)(11)(12)(13)(14) were screened for their in vitro antibacterial activity against four bacterial isolated Bacillus subtilis, Streptococcus faecalis, Micrococcus luteus, and Staphylococcus aureus. The results of the study revealed that the compounds 7-14 showed significant antibacterial potency.…”
Section: Structures Of Lamotrigine Analogs 7-10mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Moreover, the interaction between compound 3 as a strong nucleophile and cyanoacetic acid as bi-electrophile in ethanol with few drops of piperidine as a catalyst, yielded 11 (8), while treatment with 2-chloroacetonitrile in DMF, afforded 12 [1,2,4]triazin-7-yl)phenyl)pivalamide (9) respectively Scheme 4.…”
Section: Scheme 2 Synthesis Of Compounds 4 Andmentioning
confidence: 99%
“…On the other hand, phosphorusbearing 1,2,4-triazine mostly enhanced their physical, chemical, and biological properties. 7,8 Also, 3-hydrazino-6-aryl-1,2,4-triazin-5-one used to produce heterobicyclic as anti-HIV and/or molluscicidal activity against some snails. 7 As well as 3-thixio-1,2,4-traizin-5-one derivatives used as starting materials to obtain heteropolycyclic nitrogen systems as antioxidant and anti-inflammatory 9 .…”
Section: Introductionmentioning
confidence: 99%